2008
DOI: 10.1002/hipo.20486
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase C phosphorylation site on GAP‐43 differentially regulates information storage

Abstract: Protein kinase C (PKC) is known to regulate phosphorylation of substrates such as MARCKS, GAP-43 and the NMDA receptor, all of which have been linked to synaptic plasticity underlying information storage processes. Here we report on 3 transgenic mice isoforms differentiated both by mutation of the PKC site on GAP-43 as well as by their performance in 3 learning situations: 1) a radial arm maze task, which evaluates spatial memory and its retention, 2) fear conditioning which assesses contextual memory and 3) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…First, it enhances learning on a working and spatial memory version of the delayed matching-to-place task in the radial arm maze (Routtenberg et al 2000) but not on purely spatial tasks, such as contextual fear conditioning or the water maze (Holahan and Routtenberg 2008). However, it favors the extinction of contextual fear memory and enhances reversal learning in the radial arm maze (Holahan and Routtenberg 2008). Overexpression of a pseudophosphorylated GAP43 does not affect spatial learning but enhances contextual fear memory and blocks its extinction (Holahan and Routtenberg 2008).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…First, it enhances learning on a working and spatial memory version of the delayed matching-to-place task in the radial arm maze (Routtenberg et al 2000) but not on purely spatial tasks, such as contextual fear conditioning or the water maze (Holahan and Routtenberg 2008). However, it favors the extinction of contextual fear memory and enhances reversal learning in the radial arm maze (Holahan and Routtenberg 2008). Overexpression of a pseudophosphorylated GAP43 does not affect spatial learning but enhances contextual fear memory and blocks its extinction (Holahan and Routtenberg 2008).…”
Section: +mentioning
confidence: 99%
“…Consistently, GAP43 overexpression has an effect on memory. First, it enhances learning on a working and spatial memory version of the delayed matching-to-place task in the radial arm maze (Routtenberg et al 2000) but not on purely spatial tasks, such as contextual fear conditioning or the water maze (Holahan and Routtenberg 2008). However, it favors the extinction of contextual fear memory and enhances reversal learning in the radial arm maze (Holahan and Routtenberg 2008).…”
Section: +mentioning
confidence: 99%
“…GAP-43 homozygous deficit mice die shortly after birth (Strittmatter et al, 1995, Maier et al, 1999, while homozygous GAP-43 overexpressing mice show enhanced learning and synaptic plasticity (Routtenberg et al, 2000). Also, transgenic GAP-43 overexpressing mice exhibit deficit spatial learning (Holahan and Routtenberg, 2008) when observed in radial arm maze, Morris water maze and contextual fear conditioning. However, Holahan and Routtenberg (2008) demonstrated that the phosphorylation state of GAP-43 plays a key role in the regulation of its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, transgenic GAP-43 overexpressing mice exhibit deficit spatial learning (Holahan and Routtenberg, 2008) when observed in radial arm maze, Morris water maze and contextual fear conditioning. However, Holahan and Routtenberg (2008) demonstrated that the phosphorylation state of GAP-43 plays a key role in the regulation of its activity. Significant memory impairments was observed in heterozygous GAP-43 knockout mice with levels reduced by one-half, but with normal levels of synaptophysin (Rekart et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The overall behavioral memory functions associated with each of these lines has been reported; 104 G-Phos mice showed enhanced …”
Section: Relationship To Memory Storagementioning
confidence: 99%